PENINGKATAN KAPASITAS PEMERINTAH DESA TUMBANG TARUSAN KABUPATEN PULANG PISAU MELALUI SISTEM INFORMASI DESA - Ameylia Selvi, Marchel; Jaya, Imanuel; Zulfauzan, Ricky (Journal Ilmu Sosial, Politik dan Pemerintahan, 2021)
Efforts to increase the capacity of the village government through the village information system are an ability of the village government to carry out tasks and functions in the application of the village information system to achieve the goal of improving public services. The purpose of this study is to examine and explain the efforts made by the village government in implementing the information system in Tumbang Tarusan Village, Banama Tingang District, Pulang Pisau Regency. The consideration that underlies this research is that the Tumbang Tarusan village government is supported by the Pulang Pisau district government in implementing the information system in accordance with the program that has been prepared. In this study, the author uses a theoretical model of E-Government, one of which is to improve public services in a better direction. To achieve these benefits, it is measured by aspects of the E-Government application according to Rianto and Tri Lestari, namely hardware, software, data and information, and communication. The results of this study indicate efforts to improve village information systems as well as strategies to achieve goals that are used to involve the community, planning is carried out on the basis of shared goals. The supporting factors are the availability of a village information system supported by the district government, cooperation between village institutions, community involvement, village apparatus resources and internet network access.